2007
DOI: 10.1186/1472-6750-7-18
|View full text |Cite
|
Sign up to set email alerts
|

RNA mutagenesis yields highly diverse mRNA libraries for in vitro protein evolution

Abstract: Background: In protein drug development, in vitro molecular optimization or protein maturation can be used to modify protein properties. One basic approach to protein maturation is the introduction of random DNA mutations into the target gene sequence to produce a library of variants that can be screened for the preferred protein properties. Unfortunately, the capability of this approach has been restricted by deficiencies in the methods currently available for random DNA mutagenesis and library generation. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Substitution S268G is far less common among clinical isolates (present only in TEM‐49 and TEM‐136). This substitution was found in five different experimental studies: four using cefotaxime as a selective agent (Holloway et al , 2007; Kopsidas et al , 2007; Bershtein & Tawfik, 2008; M.L.M. Salverda & J.A.G.M.…”
Section: Comparison Of the Natural And Laboratory Evolution Of Tem‐1mentioning
confidence: 86%
See 1 more Smart Citation
“…Substitution S268G is far less common among clinical isolates (present only in TEM‐49 and TEM‐136). This substitution was found in five different experimental studies: four using cefotaxime as a selective agent (Holloway et al , 2007; Kopsidas et al , 2007; Bershtein & Tawfik, 2008; M.L.M. Salverda & J.A.G.M.…”
Section: Comparison Of the Natural And Laboratory Evolution Of Tem‐1mentioning
confidence: 86%
“…The detailed description of the natural evolution of TEM alleles, combined with the experimental ease of selecting for increased antibiotic resistance, has made TEM-1 a frequently used tool for exploring the potential of novel protein engineering techniques (Stemmer, 1994;Zaccolo & Gherardi, 1999;Long-McGie et al, 2000;Camps et al, 2003;Fujii et al, 2004;Kopsidas et al, 2007). Soon, the potential of using in vitro evolution to repeat or even predict the natural evolution of TEM-1 was recognized (Vakulenko et al, 1998), and, by adjusting the mutational spectrum and enzyme expression levels, in vitro evolution protocols were further fine tuned in order to mimic the natural evolutionary process (Barlow & Hall, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The low fidelity of the MS2 replicase makes it suitable for direct in vivo or in vitro generation of RNA libraries for protein or aptamer selection from clonal RNA templates without the need for DNA mutagenesis. A study describing the in vivo use of Qβ replicase to generate mRNA libraries showed that the mutational spectrum of phage RNA replicases is close to the ideal (67). Furthermore, the independence of the MS2 RdTT system from DNA might increase the repertoire of selection strategies for DNA-modifying enzymes such as DNA nucleases, ligases, polymerases, recombinases or methyltransferases whose activity can interfere with a conventional DNA construct.…”
Section: Discussionmentioning
confidence: 99%
“…M182T is a stabilizing mutation [28] that is found clinically in resistant alleles to a wide variety of -lactamase substrates and inhibitors but never appears alone [43]. In most directed evolution experiments for increased resistance to cefotaxime, M182T appears after G238S [44][45][46][47][48][49]. M182T-induced stabilization has been shown to have compensatory effects for a wide variety of mutations for amoxicillin resistance [22].…”
Section: S3mentioning
confidence: 99%